2021
DOI: 10.1371/journal.pone.0256810
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive versus liberal transfusion thresholds in very low birth weight infants: A systematic review with meta-analysis

Abstract: Background To assess the efficacy and safety of restrictive versus liberal red blood cell transfusion thresholds in very low birth weight infants. Methods We searched MEDLINE, EMBASE, and Cochrane database without any language restrictions. The last search was conducted in August 15, 2020. All randomized controlled trials comparing the use of restrictive versus liberal red blood cell transfusion thresholds in very low birth weight (VLBW) infants were selected. Pooled risk ratio (RR) for dichotomous variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…Although the data from the initial studies was conflictive [2,3], two larger recently published randomized trials (TOP and ETTNO) found no differences between the liberal and restrictive transfusion groups in the primary outcome of death or neurodevelopmental impairment at 24 months of age [4 ▪▪ ,5 ▪▪ ]. In contrast to prior observational studies, which had reported an association between RBC transfusions and both bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) (diseases of prematurity with a strong inflammatory component) [6], none of the randomized trials found increased rates of those or other complications in neonates transfused more liberally [7]. However, the neurodevelopmental outcomes evaluated in the RCTs measured severe deficits, and it remains unclear whether RBC transfusions (or anemia) are associated with more subtle neurodevelopmental problems (i.e.…”
Section: Red Blood Cell Transfusions In Neonatesmentioning
confidence: 81%
See 1 more Smart Citation
“…Although the data from the initial studies was conflictive [2,3], two larger recently published randomized trials (TOP and ETTNO) found no differences between the liberal and restrictive transfusion groups in the primary outcome of death or neurodevelopmental impairment at 24 months of age [4 ▪▪ ,5 ▪▪ ]. In contrast to prior observational studies, which had reported an association between RBC transfusions and both bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) (diseases of prematurity with a strong inflammatory component) [6], none of the randomized trials found increased rates of those or other complications in neonates transfused more liberally [7]. However, the neurodevelopmental outcomes evaluated in the RCTs measured severe deficits, and it remains unclear whether RBC transfusions (or anemia) are associated with more subtle neurodevelopmental problems (i.e.…”
Section: Red Blood Cell Transfusions In Neonatesmentioning
confidence: 81%
“…]. In contrast to prior observational studies, which had reported an association between RBC transfusions and both bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) (diseases of prematurity with a strong inflammatory component) [6], none of the randomized trials found increased rates of those or other complications in neonates transfused more liberally [7]. However, the neurodevelopmental outcomes evaluated in the RCTs measured severe deficits, and it remains unclear whether RBC transfusions (or anemia) are associated with more subtle neurodevelopmental problems (i.e.…”
Section: Andandmentioning
confidence: 86%
“…Several meta-analyses [25][26][27][28] have compared the efficacy and safety of restrictive versus liberal transfusion thresholds.…”
Section: Comparison With Previous Meta-analysesmentioning
confidence: 99%
“…A series of previous randomized controlled trials (RCTs) have investigated the impact of different transfusion thresholds on clinical outcomes of anemic preterm infants but reported conflicting results [22][23][24]. Subsequently, several meta-analyses [25][26][27][28] have further evaluated the comparative efficacy and safety of restrictive versus liberal transfusion thresholds for treating anemic preterm infants and suggested that restrictive transfusion threshold was comparable to liberal transfusion threshold in death and neurodevelopment. However, the value of these findings dedicated to making the clinical decision was limited because several clinically important outcomes were not evaluated in previous meta-analyses, such as age at first transfusion, total transfusion volume, and time on supplemental oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Geçmişte kısıtlı ve liberal transfüzyonla ilgili yapılan en önemli randomize kontrollü iki çalışma IOWA ve PINT çalışmalarıdır [16,25,26] rapor edilmiştir [29]. Mevcut bulgular ışığında ve TND 2021 güncellemesinin de önerisiyle prematüre bebeklerde kısıtlı transfüzyon yaklaşımının uygulanması daha uygun gibi gözükmektedir [16].…”
Section: Yenidoğanda Optimal Eritrosit Transfüzyon Eşik Hb/htc Değerleri Nedir?unclassified